The effects of healthy sleep campaign towards the intention to practice healthy sleep behaviour in managing obesity among Malay women - Mamat, Absah; Ab Karim, Mohamad Shahrim; Mohamad, Zainal Abidin; Jamaluddin, Rosita; Ungku Zainal Abidin, Ungku Fatimah (Global Academic Excellence, 2018)
In today’s climate, obesity management should be extended beyond the conventional manner of the sole emphasis on diet and exercise. The newly-emerging issues of sleep in the current obesity prevalence would benefit from being highlighted as an important indicator in managing the medical condition via lifestyle changes. Therefore, this called for the positioning of sleep in a form of a campaign to create awareness regarding the gravity behind healthy sleep. With that mentioned, this study looked into the effect of Healthy Sleep Campaign towards the intention to practice healthy sleep behaviour in order to lose weight, using the Theory of Planned Behaviour. The one-time campaign was executed with the participation of 400 obese Malay women aged between 18 and 55 years old in the state of Melaka, where they were asked to complete a survey form. Such step appeared to be integral in measuring whether the knowledge gained from the campaign was indeed capable of influencing their respective intentions to perform healthy sleep behaviour in achieving weight loss. Subsequent statistical analysis was undertaken for both the measurement and structural models respectively using the Partial Least Square Structural Equation Model (PLS-SEM). Based on the analysis, the Healthy Sleep Campaign was found to pose a significantly direct influence on all predictors in the study. Furthermore, it was also capable of moderating the relationship between the predictors towards the intention to practice healthy sleep behaviour. However, the study was primarily limited by the measurement, as it was focused on the intention to perform healthy sleep behaviours instead of looking into the actual behavioural changes themselves. Nevertheless, the results indicated important implications regarding the possible planning and implementation of healthy sleep campaign in a structured manner alongside lifestyle practices in managing obesity beyond diet and exercising. Moreover, suggestions for future research were also made specifically in measuring behavioural changes towards healthy sleep as a new weight loss factor, as well as exploring the impacts of healthy sleep behaviour in managing obesity.